Loyal activists?: Party socialization and dissenting voting behavior in parliament - Mai, Philipp; Wenzelburger, Georg (Legislative studies quarterly, 2024)
The question of why members of parliament (MPs) overwhelmingly toe the party line is receiving increasing scholarly attention. Adding to discipline-based approaches, party loyalty, that is, a feeling of allegiance not related to policy agreement or disciplinary pressures, is an important part of the explanation. In this article, we employ a more nuanced view on party loyalty than previous observational studies and conceptualize it as the result of socialization processes of most politicians into the structures of their party prior to their mandate. We test our argument quantitatively using data for whipped votes in the German Bundestag (1949-2017). The results support our propositions that MPs who didn't hold party offices prior to their mandate have a higher probability of vote defection and that the behavioral differences related to pre-parliamentary socialization vanish the longer MPs serve in parliament. Our work has important implications for research on intraparty politics, legislative behavior, and representation.